2014
DOI: 10.1158/0008-5472.can-13-1443
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Functions and Interdependency of the DNA-Binding Domain of BRCA2 with the BRCA1–PALB2–BRCA2 Complex

Abstract: BRCA1, BRCA2, and PALB2 are key players in cellular tolerance to chemotherapeutic agents, including camptothecin, cisplatin, and PARP inhibitor. The N-terminal segment of BRCA2 interacts with PALB2, thus contributing to the formation of the BRCA1-PALB2-BRCA2 complex. To understand the role played by BRCA2 in this complex, we deleted its N-terminal segment and generated suggesting that the N-terminal segment and the DBD play a substantially overlapping role in the functionality of BRCA2. We also showed that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Interestingly, it has been suggested that both the amino-terminal domain of Brh2 and DNA act together to evict Dss1 from its C-terminal interaction surface to reveal the full DNA binding potential of Brh2 (Zhou et al, 2012; Zhou et al, 2009b). In contrast, the DBD of BRCA2 is indispensable for function both in vitro and in cells (Al Abo et al, 2014; San Filippo et al, 2006; Siaud et al, 2011). The results described herein enhance our understanding of these differences, and also furnish strong evidence that DSS1 must be stably associated with BRCA2 to be functional (Figure 1 & 5; Figure S5), and that it targets the RPA-ssDNA complex via physical interaction with RPA and acts as a DNA mimic to promote RPA-RAD51 exchange on ssDNA (Figure 2, 3, 7 & S7).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that both the amino-terminal domain of Brh2 and DNA act together to evict Dss1 from its C-terminal interaction surface to reveal the full DNA binding potential of Brh2 (Zhou et al, 2012; Zhou et al, 2009b). In contrast, the DBD of BRCA2 is indispensable for function both in vitro and in cells (Al Abo et al, 2014; San Filippo et al, 2006; Siaud et al, 2011). The results described herein enhance our understanding of these differences, and also furnish strong evidence that DSS1 must be stably associated with BRCA2 to be functional (Figure 1 & 5; Figure S5), and that it targets the RPA-ssDNA complex via physical interaction with RPA and acts as a DNA mimic to promote RPA-RAD51 exchange on ssDNA (Figure 2, 3, 7 & S7).…”
Section: Discussionmentioning
confidence: 99%
“…One of these proteins is P artner a nd L ocalizer of B RCA 2 (PALB2), which binds to the N-terminal region of BRCA2 and is necessary for proper sub-nuclear localization of BRCA2 [ 13 ]. In vitro studies have suggested PALB2 to be essential for many functions of BRCA2, such as G2/M checkpoint, replication fork protections, as well as repair of double strand breaks by HR [ 7 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the binding of PALB2 to BRCA2 is considered vital for BRCA2 function, recent studies have suggested that there may exist a functional redundancy between the PALB2-binding domain and the C-terminal DNA-binding domain of BRCA2. In chicken DT40 cells, when the PALB2-binding N-terminal region of BRCA2 was deleted, it resulted in a mild reduction in HR and a mild sensitivity to IR, camptothecin, cisplatin as well as olaparib, a PARP1 inhibitor [ 14 ]. These cells proliferated with nearly normal kinetics and had a mild increase in the number of spontaneous chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in BRCA2 , a gene involved in recombination and repair, lead to a high risk of breast and ovarian cancer when inherited in the germ line and thus present in all somatic cells. However, cell lines with deletion of both copies of BRCA2 show a consistent growth disadvantage compared to wild-type lines (8). This may help explain why BRCA2 mutations are not significantly enriched in sporadic breast cancers (9,10).…”
Section: Mutations Which Are Predisposing But Not Advantageousmentioning
confidence: 99%